2023
DOI: 10.1111/jfs.13055
|View full text |Cite
|
Sign up to set email alerts
|

Contamination of beef and beef products by Listeria spp. and molecular characterization of L. monocytogenes in Mpumalanga, South Africa

Abstract: This study determined the prevalence, risk factors, and molecular characteristics of Listeria species detected in beef and beef products sampled in Mpumalanga province, South Africa. Four hundred beef and beef products were collected from 30 retail outlets in three districts (Bronkhorstspruit, Emalahleni, and Middelburg) within the province. Standard bacteriological and polymerase chain reaction (PCR) assays were used in the study. The overall prevalence of L. monocytogenes and other Listeria spp. in the sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 78 publications
1
1
0
Order By: Relevance
“…The ground beef samples included in the current study had an L. monocytogenes prevalence of 10% (6/60). These results are similar to those reported in other studies, like 7.3% in South Africa [ 69 ], 8.9% in India [ 64 ], 9.0% in the United States [ 70 ], 9.1% in China [ 71 ], 14% in Brazil [ 72 ], and 14% in Egypt [ 44 ]. According to these comparisons, beef appears to be treated in the same way and with the same hygiene handling processes.…”
Section: Discussionsupporting
confidence: 92%
“…The ground beef samples included in the current study had an L. monocytogenes prevalence of 10% (6/60). These results are similar to those reported in other studies, like 7.3% in South Africa [ 69 ], 8.9% in India [ 64 ], 9.0% in the United States [ 70 ], 9.1% in China [ 71 ], 14% in Brazil [ 72 ], and 14% in Egypt [ 44 ]. According to these comparisons, beef appears to be treated in the same way and with the same hygiene handling processes.…”
Section: Discussionsupporting
confidence: 92%
“…Our fndings that L. monocytogenes contaminated 9.3% of the beef and beef products tested have food safety implications for consumers because L. monocytogenes, the most important species of Listeria, is frequently associated with cases and outbreaks of human listeriosis [44]. A similar prevalence of 8.3% for L. monocytogenes was reported for beef and beef products (raw beef, RTE, milled beef, ofal, and organs) sampled at retail outlets in Mpumalanga province, South Africa [45]. However, Matle et al [10] reported a higher pathogen prevalence (14.7%) in the country's meat products.…”
Section: Discussionmentioning
confidence: 67%